2022
DOI: 10.1038/s41598-022-15604-w
|View full text |Cite
|
Sign up to set email alerts
|

Low-profile dual-band pixelated defected ground antenna for multistandard IoT devices

Abstract: A low-profile dual-band pixelated defected ground antenna has been proposed at 3.5 GHz and 5.8 GHz bands. This work presents a flexible design guide for achieving single-band and dual-band antenna using pixelated defected ground (PDG). The unique pixelated defected ground has been designed using the binary particle swarm optimization (BPSO) algorithm. Computer Simulation Technology Microwave Studio incorporated with Matlab has been utilized in the antenna design process. The PDG configuration provides freedom … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…It is also found that the BPSO algorithm converges faster than other algorithms because it is more targeted in each searching direction and avoids getting stuck in local optima [20,22]. The BPSO algorithm has also been successfully used in pixelated structures [23][24][25][26][27]. The BPSO algorithm has a population (called a swarm) of candidate solutions (called particles) which move in the search space of the problem.…”
Section: Unit Cell Designmentioning
confidence: 99%
“…It is also found that the BPSO algorithm converges faster than other algorithms because it is more targeted in each searching direction and avoids getting stuck in local optima [20,22]. The BPSO algorithm has also been successfully used in pixelated structures [23][24][25][26][27]. The BPSO algorithm has a population (called a swarm) of candidate solutions (called particles) which move in the search space of the problem.…”
Section: Unit Cell Designmentioning
confidence: 99%
“…However, a detailed analysis shows that the threshold for small antennas is in fact k a ≤ 0.5 [31,32]. With L as the maximum dimension of the antenna and a the radius of the sphere enclosing the antenna, as shown in Figure 7, the following expression can be easily derived: 6 Depicted is (a) an exemplary antenna of the dataset as present in Sonnet, (b) a delta-gap port used in Sonnet for differential feeding, as well as (c) a produced antenna of our dataset with an antenna size of k a = 0.51 and a cross size of S cross /λ = 0.64%.…”
Section: Antenna Sizementioning
confidence: 99%
“…Pixelated antennas have become an interesting research topic in the last decade, as exemplified by a variety of different publications focusing on different application scenarios and design-and optimisation techniques [1][2][3][4][5][6][7]. In principle, they simply consist of individual conducting elements (pixels), that can be interconnected to create an antenna.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Different attempts have been made by the antenna research community to improve isolation. The defected ground structure (DGS) is a common technique for reducing mutual coupling [13][14][15]. Nevertheless, antenna radiation performance is impacted when the DGS is used as a decoupling element.…”
Section: Introductionmentioning
confidence: 99%